Effect of a training programme on knowledge and practice of lifestyle modification among hypertensive patients attending out-patient clinics in lagos - Oluwatosin Mary Oyewole; Olaolorunpo Olorunfemi; Foluso Ojewole; Mojolaoluwa Omolade Olawale (Wolters Kluwer Medknow Publications, 2020)
Background: Hypertension is the leading cause of cardiovascular disease and death in the world. Research shows that the best way to remediate this problem is through lifestyle modification, but the percentage of hypertensive patients with the right knowledge about life-style modification is very low. It is therefore imperative to develop different ways of improving the practice and knowledge of life-style modification. Consequently, this study aim to determine the effectiveness of a training programme on knowledge and practice of lifestyle modification among hypertensive patients. Materials and Methods: A quasi-experimental design was conducted with accidental sampling to select the sample size (n = 30). A modified structured questionnaire from World Health Organization (WHO), Hypertension Knowledge-Level Scale (HK-LS) were used to measure knowledge of hypertension, knowledge of lifestyle modification and practice. Tables, percentages, mean, Standard Deviation and t-test were used for data analysis at 0.05 levels of significance, through statistical package for the social science software. Results: The result showed that the t-test of the pre-knowledge about hypertension among hypertensive patients differed significantly from post-knowledge after intervention (t = 4.90, p = 0.001). In addition, there is significant different between the pre and post knowledge level about lifestyle modification after intervention (t = 3.62, p = 0.001). Significant different was also observed between the pre and post practice of lifestyle medication after intervention (t = 3.56, p = 0.001). Conclusions: The health care providers, especially the nurses, must provide a continuous and focused training programme for hypertensive patients in order to improve their knowledge and practice of lifestyle modification.